Pediatric Obesity and Eating Disorders Symptoms: The Role of the Multidisciplinary Treatment. A Systematic Review - De Giuseppe, Rachele; Di Napoli, Ilaria; Porri, Debora; Cena, Hellas (Frontiers in Pediatrics, 2019)
The prevalence of obesity in children/adolescents has increased worldwide during the past 30 years, becoming a significant public health concern; prevention and management of pediatric obesity onset is one of the most critical public health goals for both industrialized and developing countries. Pediatric obesity has been identified as a risk factor for various psychopathologies, including eating disorders (ED). Although it has been demonstrated that a comprehensive multidisciplinary treatment (MT), with small steps and practical approaches to lifestyle change, can be an effective treatment for children and adolescents with obesity, to the best of our knowledge, this is the first systematic review investigating the effect of MT on the development, progression or decrease of ED symptoms (EDS) in this target population. PubMed and Web of Science databases were searched (last search on 18 February 2019) according to a predetermined search strategy, in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Guidelines and Statement. Original studies published in English examining the effect of MT on pediatric overweight/obesity, paying particularly attention at the development of EDS, were eligible for inclusion. Seven hundred and forty-four records have been identified; nine articles with study quality ranging from weak to moderate have been included. MTs were heterogeneous in nature including length, number, frequency and type of sessions, parent-involvement and use of technology, besides several psychometric questionnaires were used to screen for EDS, since there are no standardized criteria. In 3 studies there was a significant decrease in external and emotional eating and in four studies a significant increase in restraint eating post MT. Two studies found a significant decrease of binge eating symptoms and other two studies showed an improvement of self-perception, weight and shape concern. A statistical significant decrease in BMI, BMIz, BMISDS and adjusted BMI was observed after all MTs, except one. A narrative summary of the evidences reported highlighted the positive impact of MT on the EDS. Moreover, since weight loss post MTs was not necessarily related to EDS, clinicians should also look for the presence of EDS and treat them accordingly.